A Single Domain in Human DNA Polymerase ι Mediates Interaction with PCNA: Implications for Translesion DNA Synthesis - Haracska, Lajos (American Society for Microbiology, 2005)
DNA polymerases (Pols) of the Y family rescue stalled replication forks by promoting replication through DNA lesions. Humans have four Y family Pols, η, ι, κ, and Rev1, of which Pols η, ι, and κ have been shown to physically interact with proliferating cell nuclear antigen (PCNA) and be functionally stimulated by it. However, in sharp contrast to the large increase in processivity that PCNA binding imparts to the replicative Pol, Polδ, the processivity of Y family Pols is not enhanced upon PCNA binding. Instead, PCNA binding improves the efficiency of nucleotide incorporation via a reduction in the apparent K(m) for the nucleotide. Here we show that Polι interacts with PCNA via only one of its conserved PCNA binding motifs, regardless of whether PCNA is bound to DNA or not. The mode of PCNA binding by Polι is quite unlike that in Polδ, where multisite interactions with PCNA provide for a very tight binding of the replicating Pol with PCNA. We discuss the implications of these observations for the accuracy of DNA synthesis during translesion synthesis and for the process of Pol exchange at the lesion site.